2015
DOI: 10.1007/s00784-015-1490-8
|View full text |Cite
|
Sign up to set email alerts
|

One-year evaluation of inactive occlusal enamel lesions in children and adolescents

Abstract: Occlusal surfaces harboring inactive caries lesions did not require additional attention than the one normally given to sound occlusal surfaces over a 1-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Furthermore, the annual Brestoration^rate for iCCLs was 4.3%. Although to date no comparable long-term data for iCCLs is available, previous studies on occlusal caries lesions [24,25] seem to be in agreement with the present result. In the first study, 478 of 491 inactive lesions (97%) did not progress within 1 year [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the annual Brestoration^rate for iCCLs was 4.3%. Although to date no comparable long-term data for iCCLs is available, previous studies on occlusal caries lesions [24,25] seem to be in agreement with the present result. In the first study, 478 of 491 inactive lesions (97%) did not progress within 1 year [25].…”
Section: Discussionsupporting
confidence: 92%
“…Although to date no comparable long-term data for iCCLs is available, previous studies on occlusal caries lesions [24,25] seem to be in agreement with the present result. In the first study, 478 of 491 inactive lesions (97%) did not progress within 1 year [25]. In the second study, about 90% of the inactive lesions remained inactive over a study period of 3 years [24].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are important in light of the current understanding of caries activity and the need for intervention. Dental surfaces are continuously undergoing the de‐remineralisation process and, in this context, an inactive lesion is a self‐controlled demineralisation process that does not tend to progress. Therefore, the added benefit of including inactive lesions in new caries indices seems questionable, mainly when epidemiological data will be used to estimate treatment needs in populations.…”
Section: Discussionmentioning
confidence: 99%
“…Hintze [20] reported progression to cavitation of 22% and to filling of 8% of the enamel lesions (from baseline mean age 14.5 years to follow-up 17.6 years). Zenkner et al [21] reported that, out of 539 inactive enamel lesions at baseline, 3% progressed to active lesions and 1% were filled after 1 year (baseline median age 13) based on thorough clinical examinations [16,21].…”
Section: Regressionmentioning
confidence: 99%
“…Moreover, considering the fact that caries management strategies in dentistry recently have become more focused toward prevention and conservative approaches, assessing non-cavitated lesions is essential for complete understanding of the true treatment needs of patients and populations [15]. Even though there is some research published on similar topics worldwide [14][15][16][17][18][19][20][21][22][23][24], there is none specifically related to the prevalence and progression of non-cavitated carious lesions in permanent teeth, particularly in the United States [17,25,26]. Therefore, it is important to study caries progression and differences by age.…”
Section: Introductionmentioning
confidence: 99%